Dbałość o moralną kondycję społeczeństwa versus wolność mediów – o tym, jak Turcja przekracza kolejne granice - Szkudlarek, Magdalena (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The aim of this article is to examine reasons and circumstances of Turkish state’s increasing interference in freedom of mass media and to present tools that are being used in this process and its consequences. However, on the contrary to majority of this type of analysis – the subject of examination is not political censorship referring to Kurdish and Armenian cases but limitation of these contents which are not consistent with ethos of Muslim society. Method that was used in order to ensure a comprehensive presentation of this subject is legal analysis of the statements issued by Turkish Radio and Television Supreme Council (RTÜK) which is entitled to fine the broadcaster or even to demand to stop broadcasting. In the second part of the analysis there are discussed examples of TV programs like cartoons The Simpsons or Winnie the Pooh which regardless of its “indecency” became an object of interest of the RTÜK.